2016
DOI: 10.1080/01658107.2016.1183133
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Vestibular Schwannoma: A Case of Optic Disc Oedema without Hydrocephalus

Abstract: A wide range of pathologies can cause papilloedema. Vestibular schwannoma is a benign and slow-growing tumour that causes symptoms and findings on ophthalmic examination when the diagnostic is delayed. The authors report a case of a 64-year-old male who presented with bilateral disc oedema secondary to a vestibular schwannoma grade 4. Obstructive hydrocephalus was not evident. The authors suggest that cerebrospinal fluid protein may have a role in the formation of optic disc oedema. A right suboccipital cranie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Matos et al reported a case of optic disc edema without hydrocephalus in a 3 cm tumor. 19 Papilledema without hydrocephalus is also described in an NF 2 case. 20 Similar observations were reported in other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Matos et al reported a case of optic disc edema without hydrocephalus in a 3 cm tumor. 19 Papilledema without hydrocephalus is also described in an NF 2 case. 20 Similar observations were reported in other studies.…”
Section: Discussionmentioning
confidence: 90%
“…More recently, Grainger and Dias [ 9 ] and Matos, et al [ 10 ] suggested that protein secretion into the CSF by vestibular schwannomas may cause an impaired reabsorption of CSF, albeit intermittently, resulting in a type of communicating hydrocephalus. The same mechanism was proposed in patients with spinal schwannomas and normal pressure hydrocephalus [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is even more rare to identify patients with papilledema without hydrocephalus, although there are isolated cases reported. [14][15][16]…”
Section: Introductionmentioning
confidence: 99%